LABORATORY FEATURES OF ACUTE VIRAL HEPATITIS IN THE REPUBLIC OF KARAKALPAKSTAN (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Acute viral hepatitis (AVH) remains a significant public health challenge in the Republic of Karakalpakstan, an area characterized by unique ecological and environmental factors associated with the Aral Sea crisis. Environmental stressors, localized water quality issues, and regional socio-demographic dynamics profoundly influence the epidemiological and clinical manifestations of hepatotropic viruses. While the clinical presentations of AVH are well-documented, a comprehensive analysis of modern laboratory phenotypes, particularly the quantitative dynamics of specific enzymatic, pigment, and immunological markers within this specific geographic cohort, is essential to optimizing diagnostic pathways and predicting clinical outcomes.
Keywords: Acute viral hepatitis, HAV, HBV, HEV, clinical features, laboratory findings, Karakalpakstan.